A Phenotypic Approach to Genitourinary Candidiasis: Correlating CHROMagar Color Profiles and Germ Tube Status with Specific Risk Factors for Targeted Intervention - Majid Jillab , Zahraa; Fadel Razouki, Ali (Hammurabi Journal of Medical Sciences, 2026)
Background: Genitourinary candidiasis, including vulvovaginal candidiasis (VVC) in women and various forms of the fungus Candida found in urine (candiduria) in men and children presents a serious, increasing global economic burden. Objectives: To identify and characterize the different Candida species isolated from vaginal swabs and urine samples using phenotypic methods. Materials and Methods: 27 samples were found to be positive for Candida species from the total 120 culured. Of the positive samples, 26 were vaginal swabs and one was a urine sample. Each of the samples was then cultured on CHROMagar™ Candida and incubated for 48 hours. Species were identified by characteristic colony coloration and morphology, supported by germ tube test. In addition, exploratory risk factor analysis was conducted to assess the association between identified species and specific clinical and demographic factors. Results: We found 5 species of Candida including C. albicans (59.3%, n=16), C. tropicalis (18.5%, n=5), C. krusei (11.1%, n=3), C. glabrata (7,4%, n=2) and C. dubliniensis (3,7%, n=1). C. tropicalis isolates varied in color presentation including metallic-blue, whitish-copper, and white-metallic blue phenotypes. C. dubliniensis showed characteristic dark green color that was easily separated from the light green C. albicans species. Conclusion: C. albicans was the most commonly identified species (59.3%), followed by C. tropicalis (18.5%), C. krusei (11.1%), C. glabrata (7.4%) and C. dubliniensis (3,7%). Species identification was 100% concordant on germ tube and CHROMagar™ Candida. The C. albicans were most common in regards to UTIs, pregnancy and COVID-19 history, while the C. tropicalis had a strong predilection for UTIs (80%). A combination of these phenotypic approaches accurately identified the species in a rapid, inexpensive manner that is necessary to guide appropriate antifungal therapy.